Penggunaan Smartphone dan Implikasinya terhadap Kesehatan Mental Remaja: Scooping Review - Oktavia Lestari Assa; Irne Wida Desiyanti; Adhe Lisna Gayuh Sasiwi (Jurnal Ners, 2025)
Mental health is an important issue because more than half of young people experience mental health disorders such as anxiety, depression or other mental health problems. One of the main factors contributing to this mental health problem is excessive smartphone use. The aim of this research is to determine the effect of smartphone and the implications on adolescent mental health. This research used Scoping Review Method. The inclusion criteria for scoping source searches are articles that discuss smartphone use and the implications for adolescent mental health. The year of publication of the articles used is 2019 – 2024, in English and Indonesian language. The search keywords are smartphone OR mobile phone AND school OR student AND mental health OR anxiety OR depression. Scoping review analysis using PEO (Population, Exposures, Outcomes). The research results were based on the total number of articles used for review, 5 of the 502 articles that met the inclusion criteria. In conclusion, several findings in the scoping review include the problem of excessive smartphone use in physical health and mental health efforts to overcome it. Keywords: Smartphone, Mental Health, Implication, Adolescent..